Foundations of legal negotiations - Stelmach, Jerzy; Brożek, Bartosz (Studies in the philosophy of law ;, 2014)
This collection of essays written by leading philosophers, lawyers, economists, and psychologists - deals with the various dimensions of legal negotiations. The contributions concern the logical structure of legal negotiations, as well as the possible philosophical assumptions behind the process of negotiating. The book also covers the problem of economic mechanisms and the psychological underpinnings of negotiating in the shadow of the law, addressing both conceptual and practical issues. (Series: Studies in the Philosophy of Law - Vol. 8).